2022
DOI: 10.1002/hpja.608
|View full text |Cite
|
Sign up to set email alerts
|

“They loved gambling more than me.” Women's experiences of gambling‐related harm as an affected other

Abstract: Background Gambling poses a global threat to public health due to its far‐reaching impacts. Research has demonstrated a ripple effect of harmful gambling on social network members and broader communities. While researchers have documented extreme harms associated with an affected other, limited research has qualitatively investigated how women describe their concerns about the gambling of a social network member, and any subsequent negative impacts on their own lives. Methods An online panel survey was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Many gambling products are linked to issues of major community concern including family violence, homelessness, energy poverty, mental health problems and suicide (see 8 ). These harms impact not only on the individual gambler, but also on their social network members 9 . Prolific and omnipresent gambling marketing has also led to the normalisation of gambling for children and young people, who are now exposed to gambling products and promotions in everyday community settings, and consider gambling a normal or common part of sport 10 .…”
Section: Gambling Products Are Linked To Some Of Our Most Pressing He...mentioning
confidence: 99%
“…Many gambling products are linked to issues of major community concern including family violence, homelessness, energy poverty, mental health problems and suicide (see 8 ). These harms impact not only on the individual gambler, but also on their social network members 9 . Prolific and omnipresent gambling marketing has also led to the normalisation of gambling for children and young people, who are now exposed to gambling products and promotions in everyday community settings, and consider gambling a normal or common part of sport 10 .…”
Section: Gambling Products Are Linked To Some Of Our Most Pressing He...mentioning
confidence: 99%
“…However, researchers have highlighted that they are often excluded or underrepresented in gambling studies (McCarthy et al, 2019 ). It was also important to ensure that women's experiences were represented in the study as both gamblers and affected others (McCarthy et al, 2022b , c ). All participants provided informed consent and were offered a $50 grocery voucher.…”
Section: Methodsmentioning
confidence: 99%
“…Second, there is limited understanding of the alternative frames that gamblers think could be used in public messages about gambling. Third, while there is some evidence that affected others view gambling harm as the result of individual behavior (McCarthy et al, 2022c ), no research to date has specifically explored how responsible gambling frames may impact on the perceptions held by people who have been directly impacted by someone else's gambling (‘affected others'). Finally, Alexius ( 2017 ) suggested that the members of a gambler's social network may reinforce that the gambler is responsible for harm if they have been taught that gambling is a personal responsibility.…”
Section: Introductionmentioning
confidence: 99%
“…A person might lie about their online activity to hide their sexual interests, sexual practices, or sexual compulsions from a partner or family member [33,35]. Secrecy and lying to close relations are also characterized as typical behaviors of people with gambling disorder who gamble online and offline [36,37]. Previous research found correlations between internet misuse, compulsive behaviors [29,31] and impaired relationships with family and friends [33,35] but not with scores on the Sheehan Disability Scale (a three-item self-report scale of work, family life and home responsibilities) [38].…”
Section: Introductionmentioning
confidence: 99%